Respuesta :

Answer: (51ab^2)/(20c)

STEP

1

:

Equation at the end of step 1

 ((17•(a3))•(b2)) ((18•(b4))•(c3))

 ————————————————•————————————————

 ((15•(b3))•(c2))  ((23a2•b)•c2)  

STEP

2

:

Equation at the end of step

2

:

 ((17•(a3))•(b2)) ((2•32b4)•c3)

 ————————————————•—————————————

 ((15•(b3))•(c2))    23a2bc2  

STEP

3

:

           (2•32b4c3)

Simplify   ——————————

            23a2bc2  

Dividing exponential expressions :

3.1    b4 divided by b1 = b(4 - 1) = b3

Dividing exponential expressions :

3.2    c3 divided by c2 = c(3 - 2) = c1 = c

Dividing exponents:

3.3    21   divided by   23   = 2(1 - 3) = 2(-2) = 1/22

Equation at the end of step

3

:

 ((17•(a3))•(b2)) 9b3c

 ————————————————•————

 ((15•(b3))•(c2)) 4a2

STEP

4

:

Equation at the end of step

4

:

 ((17•(a3))•(b2)) 9b3c

 ————————————————•————

   ((3•5b3)•c2)   4a2

STEP

5

:

Equation at the end of step

5

:

 (17a3 • b2)   9b3c

 ——————————— • ————

  (3•5b3c2)    4a2

STEP

6

:

             17a3b2

Simplify   —————————

           (3•5b3c2)

Dividing exponential expressions :

6.1    b2 divided by b3 = b(2 - 3) = b(-1) = 1/b1 = 1/b

Equation at the end of step

6

:

  17a3   9b3c

 ————— • ————

 15bc2   4a2

STEP

7

:

Dividing exponential expressions :

7.1    a3 divided by a2 = a(3 - 2) = a1 = a

Dividing exponential expressions :

7.2    b3 divided by b1 = b(3 - 1) = b2

Dividing exponential expressions :

7.3    c1 divided by c2 = c(1 - 2) = c(-1) = 1/c1 = 1/c

Final result :

 51ab2

 —————

  20c

ACCESS MORE